The IceCube neutrino observatory Part VI: ice properties, reconstruction and future developments - Collaboration, I; Aartsen, M; Abbasi, R; Abdou, Y; Ackermann, M; Adams, J; Aguilar, J; Ahlers, M; Altmann, D; Auffenberg, J; Bai, X; Baker, M; et al. (Sociedade Brasileira de Fisica, 2013)
Papers on ice properties, reconstruction and future developments submitted to the 33nd International Cosmic Ray Conference (Rio de Janeiro 2013) by the IceCube Collaboration.